Ethnocentrism, Intergroup Anxiety and Willingness to Communicate Between Cultures: A Study on Javanese and Madurese Ethnic Students - Lucky Abrorry; Siti Kamilatus Saidah; M. Fahmi Aufar Asyraf; Syafruddin Faisal Thohar; Endang Wahyuni (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2024)
Inter-ethnic harmony needs to continue to be maintained for the sake of national and state life. This harmony starts from the willingness to inter-cultural communication. This research aims to investigate relationship between ethnocentrism, intergroup anxiety and willingness to communicate between cultures and examine differences in terms of gender and ethnicity. Using a correlational research design, this research involved 172 student respondents at UIN Sunan Ampel Surabaya with 97 Javanese ethnic backgrounds and 75 Madurese students who were selected using a purposive sampling technique. Data collection was conducted using a questionnaire. The SFGENE-7 scale was used to measure the level of entocentrism, while the Greenland Group Anxiety Scale was used to measure intergroup anxiety, and the IWTC scale was used to measure the willingness to communicate between cultures. The results of this study indicate that ethnocentrism and intergroup anxiety have a significant negative relationship with willingness to communicate interculturally. Furthermore, there were no significant differences in the three variables tested in terms of ethnicity and gender.